PSIKOEDUKASI KESEHATAN MENTAL BERBASIS EDUKATIF-PARTISIPATORIS BAGI TENAGA KEPENDIDIKAN DAN PENGASUH PESANTREN - Khairunnisa, Nadea (Jurnal Pengabdian Kepada Masyarakat Mulia Madani Yogyakarta, 2025)
Mental health is a crucial aspect supporting a safe, productive, and meaningful educational environment. Teachers, staff, and dormitory caregivers play a strategic role in supporting children's development, particularly in madrasah environments, which also serve as religious and social educational institutions. However, many educators and caregivers lack an adequate understanding of mental health issues and strategies for addressing them. To address this need, a mental health psychoeducation program was developed at MI Ma'arif Nurul Haromain. This program aims to improve psychological literacy, emotional awareness, and basic skills in maintaining mental health, both for themselves and in assisting students. The method used is an educational-participatory approach through training, group discussions, case simulations, and collaborative reflection. The material is based on Ryff's (1989) concept of psychological well-being, which consists of six main aspects: self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth. It is hoped that this program will strengthen the psychosocial capacity of teachers, staff, and caregivers in creating a supportive and mentally friendly educational environment.